Novel study on biodegradation of malathion and investigation of mass transfer correlation using alginate beads immobilized Bacillus sp. S4 in bioreactor - Geed S.R.; Kureel M.K.; Prasad S.; Singh R.S.; Rai B.N. (My University, 2025)
In this study the external mass transfer effects on the biodegradation of malathion were studied. The experiments were performed in continuous packed bed bioreactor packed with immobilized alginate beads. The isolated bacterial species Bacillus sp. S4 was encapsulated with alginate beds. The effect of inlet flow rate (5-20 mL/h) on biodegradation of malathion (300 mg/L) was examined. At different flow rates the biodegradation rate constants were calculated by assuming the first-order biodegradation kinetics. The possible degradation routes were proposed for malathion biodegradation. The external mass transfer coefficients for biodegradation of malathion were also investigated for different values of flow rate. The mass transfer effect was correlated with the model JD = K NRe-(1-n). The novel mass transfer correlation was found as JD = 5.7 NRe-0.40 in order to predict the experimental data accurately and the model were studied with different values of n and K. The developed model would be useful for the scale up of useful industrial bioreactors. © 2018 Elsevier Ltd. All rights reserved.